The Cardio-Electrophysiological Balance Index in Cardiovascular Diseases - Aşkın, Lütfü; Tanrıverdi, Okan (Cerrahpaşa Medical Journal, 2023)
The index of the cardio-electrophysiological balance may be used to assess ventricular arrhythmogenesis. The index of cardio-electrophysiologic al balance has been associated with malignant ventricular arrhythmias. Ventricular arrhythmias caused by drugs have been connected to a new risk measure called the index of cardio-electrophysiological balance the interval from the beginning of the QRS complex to the end of the T wave (QT) interval divided by the deflections in an electrocardiogram (EKG) tracing that represent the ventricular activity of the heart (QRS) duration), which was recently tested in an animal model. The cardiac wavelength index of cardio-electrophysiological balance was considered to equal the effective refractory period multiplied by the conduction velocity. An increase or decrease in the index of cardio-electrophysiological balance could suggest an increased risk of ventricular tachycardia/fibrillation induced by torsades de pointes or non-torsades de pointes. The index of cardio-electrophysio logical balance is one of the most often used methods for measuring the cardiac waveform. Because it is noninvasive and simple to measure, index of cardio-electrophysiological balance may be used to predict ventricular arrhythmia risk. Cite this article as: Aşkın L., Tanrıverdi O. The cardio-electrophysiological balance index in cardiovascular diseases. Cerrahpaşa Med J. 2023;47(2):118-122.